1976
DOI: 10.5271/sjweh.2801
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to trichloroethylene III. Psychological functions.

Abstract: Exposure to trichloroethylene: III. Psychological functions. Scand. j. work environ. & health 4 (1976) 220-224. The effect of exposure to the solvent trichloroethylene (TRI) on the performance of tests of numerical ability, reaction time (simple and choice), and short-term memory was studied in 15 healthy male subjects. The subjects were tested individually on three different occasions during exposure to 540 and 1,080 mg/m3 of TRI in inspiratory air and under control conditions, respectively. At predetermined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In addition, ethanol consumption has been found to potentiate TCE-related CNS effects (Savolainen, 1980;Candura and Faustman, 1991). It should be noted that some studies have not found CNS effects following TCE exposure (Stewart et al, 1974b;Ettema and Zielhuis, 1975;Gamberale et al, 1976;Konietzko et al, 1976;Fielder et al, 1982;Cherry et al, 1985;Maizlish et al, 1985;Holonen et al, 1986).…”
mentioning
confidence: 94%
“…In addition, ethanol consumption has been found to potentiate TCE-related CNS effects (Savolainen, 1980;Candura and Faustman, 1991). It should be noted that some studies have not found CNS effects following TCE exposure (Stewart et al, 1974b;Ettema and Zielhuis, 1975;Gamberale et al, 1976;Konietzko et al, 1976;Fielder et al, 1982;Cherry et al, 1985;Maizlish et al, 1985;Holonen et al, 1986).…”
mentioning
confidence: 94%
“…A long series of experimental studies was undertaken at the precursor to the Swedish NIOH in collaboration between researchers from several disciplines, including chemistry, medicine, physiology, and, last but not least, psychology. This was the series of studies in which Irma Astrand and her co-workers (7) reported results regarding uptake, distribution, and elimination of the solvents, and Francesco Gamberale and his co-workers (8)(9)(10)(11)(12)(13)(14) described effects on the CNS. In these experiments, human volunteers were exposed to the solvents toluene (8), methyl chloroform (9), styrene (10), methylene chloride (11), white spirit (12), trichloroethylene (13), xylene, and ethylbenzene (14) and the behavioral effects resulting from these exposures were studied.…”
Section: Brief History Of Solvent Researchmentioning
confidence: 99%
“…Still, a search was started in our laboratory to find tests that would be more sensitive to the early prenarcotic effects from acute solvent exposure. Thus, as part of the early experimental work by Gamberale et al (8)(9)(10)(11)(12)(13)(14), a series of tests and testing equipment were designed, thereby increasing the sensitivity of the studies.…”
Section: Quantification Ofexposurementioning
confidence: 99%
“…1968;Wolff 1976). Workers exposed to styrene are reported to suffer from neurological (Gamberale & Hultengren 1974;Seppalainen 1978;Lilis et al 1978) and hepatic disorders (Hotz er al. 1980).…”
mentioning
confidence: 99%